Movimento #ficaespanhol: uma análise semântica-enunciativa sobre a política linguística de manutenção da oferta de língua espanhola nas escolas públicas do Rio Grande do Sul - Dias, Adriele Delgado (2023)
This Doctoral thesis presents a research question based on the #FicaEspanhol Moviment, considering it as a political-linguistic movement in defense of the provision of Spanish language teaching in public schools in Rio Grande do Sul (RS). The research developed aims to analyze the arguments, which highlight the reasons why the presence of Spanish at school is relevant and which constitute the texts of the motions in support of the #FicaEspanhol Moviment. The motions were produced by the City Councils of the municipalities of Rio Grande do Sul, in support of the Constitutional Amendment Project of PEC 270/2018. To develop the thesis, we seek to: discuss the historical and political-linguistic path of teaching Spanish in Brazil; present the different perspectives of language policy as a field of knowledge; discuss theoretical notions of the Historical Semantics of Enunciation; present the research corpus to analyze the arguments rewritten in the texts of the supporting motions and identify their political meanings. This thesis adopts studies in Linguistic Policy (Lagares, 2011-2018; Calvet, 2002-2007) as a theoretical-methodological contribution, highlighting their different perspectives: linguistic planning, linguistic ideologies, glottopolitics and language policy. Enunciative studies are linked to the theoretical panorama of Language Policy, based on the proposal of Event Semantics (Guimarães, 2017-2018). In this theoretical affiliation, notions such as space of enunciation, speaker and speaker as well as argumentation and argumentativeness are taken up. The analytical gesture uses the rewriting procedure to analyze how the importance of offering Spanish language teaching is rewritten and re-signified in the arguments of the texts of the supporting motions. The meanings that emerge from the arguments work to reflect on the political place of Spanish, evidenced by specific enunciation spaces of the collective manifestation represented in the texts. The analysis corpus consists of 54 support motions, from which five motions were selected that represent each region of the state of RS (North, South, East, West and Center). When cutting out the texts of the supporting motions, Enunciative Sequences (SE) were selected in which historical, political, demographic, cultural and commercial arguments were identified to reaffirm the importance of the Spanish language in the Gaucho context. The analysis of the rewritings, in the enunciative sequences, made it possible to understand the argumentative movement, which is rewritten within the text itself to say the same thing, why it is important to offer Spanish at school. Finally, it is concluded that the words of the supporting motions represent a collective voice that reaffirms the importance of offering Spanish language teaching in public schools, in a political-linguistic discourse, in defense of the valorization of Spanish in the Brazilian school system.